Specific β-Turns Precede PPIIL Structures Binding to Allele-Specific HLA-DRβ1* PBRs in Fully-Protective Malaria Vaccine Components - Bermudez, Adriana; Alba, Martha P.; Vanegas, Magnolia; Patarroyo, Manuel A.; Patarroyo, Manuel E. (Frontiers in Chemistry, 2018)
The 3D structural analysis of 62 peptides derived from highly pathogenic Plasmodium falciparum malaria parasite proteins involved in host cell invasion led to finding a striking association between particular β-turn types located in the N-terminal peripheral flanking residue region (preceding the polyproline II left-handed structures fitting into the HLA-DRβ* allele family) and modified immune protection-inducing protein structure induced long-lasting protective immunity. This is the first time association between two different secondary structures associated with a specific immunological function has been described: full, long-lasting protective immunity.